Understanding climate change awareness, social impacts, and adaptive behavior among university youth in Bangladesh - Shofik Uddin; Imran Hossain; Mahamudur Rahman Rudro; Moinuddin Zahangir (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2026)
Global warming is a major environmental concern in Bangladesh with social and economic impact, which predominantly affects younger age groups who will suffer from its long-term ramifications. The article looks into the awareness of climate change, perceptions regarding social impacts, adaptive attitudes and behavioral practices, leadership capacity and institutional support among 200 university youth in Bangladesh. Using a mixed-method, cross-sectional approach in which analysis are qualitative and quantitative, our findings indicate almost universal climate consciousness, yet only moderate scientific understanding. Youths have high risk perception and pro adaptive attitude while engaging in resource conserving, tree for planting as well as climate communicating. Leader trust and institutional trust were the most important predictors for pro-environmental behavior, and no predictive value of knowledge (awareness) was found, while attitudinally no to be helpful on predicting pro-environmental behavior. Key barriers to integration include structural limitations (e.g. lack of space), knowledge and awareness gaps, financial obstacles, a lack of vocational education training as well as indicators for youth-led projects such as green activities. The findings emphasize the need for curriculum that injects concepts of climate change into it, leadership development programs and bolstering university sustainability frameworks. This study concludes about the importance of youth empowerment through supporting institutional environment for fostering climate change adaptation and engagement in Bangladesh.